Pathophysiology of myofascial trigger points: a review of literature - Holanda, Ledycnarf; Fernandes, Aline; Cabral, Ana Clara; Santos Junior, Francisco (International Journal of Basic and Applied Sciences, 2014)
The most common source of musculoskeletal algia is the myofascial pain syndrome (MPS), its occurrence is related to excessive involuntary muscle contraction and is characterized by hardened regions. Myofascial trigger points (MTP) are hypersensitive nodules that refer pain spontaneously or under mechanical stimuli, present in 37 % of men and 65 % women, and may be classified as: active, latent, satellite, central junction. Assuming this pathological situation affects high number individuals may cause functional impairment and compromised quality life realized the need enlarge and update searches about MTP physiology. This literature review was conducted in English, Portuguese, and Spanish articles, published since 2009 (trigger points, musculoskeletal pain, MPS) in electronic databases: Bireme, PEDro and Scielo, and a book 2007. There are four important assumptions about the pathogenesis and pathophysiology of MTP: muscle spindle, the neuropathic process, scar tissue and terminal buttons and dysfunctional energy crisis. Most studies have only two classifications for MTP: active and latent, and few describe in great detail about the possible hypotheses of the pathogenesis of these. Recent literature is sparse regarding the physiology and aetiology, however, recent studies have sought to understand the pathophysiology ensure that the hypothesis with the highest validity.